Pengaruh Diversifikasi, Manajemen Laba, Risiko Bisnis, Siklus Hidup Perusahaan Dan Non Debt Tax Shield (Ndts) Terhadap Struktur Modal - Luthfi, Muhammad; Ichdan, Dany Amrul; Pratama, Iwan Saputra (Universitas Malahayati, 2021)
This study aims to determine Diversification, Profit Management, Business Risk, Company Life Cycle and Non Debt Tax Shield (NDTS) Against Capital Structure. The object of this research is Manufacturing Companies listed on the Indonesia Stock Exchange. Based on the purposive sampling method, obtained research samples were conducted on 105 samples of manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2016-2018. Hypothesis testing in this study was carried out by using multiple regression analysis methods in the application of Eviews 8.0 program.The results showed that Diversification did not affect the Capital Structure with a significant value of 0.3349. Earnings Management Variable affects the capital structure with a significant value of 0.003. The Business Risk variable does not affect the Capital Structure with a significant value of 0.3931. The Company's Lifecycle variable does not affect the capital structure with a significant value of 0.697. Non Debt Tax Shield (NDTS) variable influences the Capital Structure with a significant value of 0.0464.Keywords: Diversification, Profit Management, Business Risk, Corporate Life Cycle, Non Debt Tax Shield (NDTS) and Capital Structure..